Comunicação e poder: a implantação do Correio Marítimo de 1798 e as respostas dos governos da América Portuguesa - Mayra Guapindaia (Nuevo mundo - Mundos Nuevos, 2017)
This article deals with communications between the Portuguese Crown and the governors of the captaincies of America on the 1798’s reform of the Maritime Post. The legislation about these reforms was accompanied by intense communicative production of the captaincy governments either before or after its launch. Based on the recent historiography on the distribution of power in the Portuguese Empire, the article tried to demonstrate that both the construction of the norms and its application was made from a dialogical process between the centre of the Monarchy and its local representatives.